Music to my ears, but words to my eyes? Text, opera and their audiences - Desblache, Lucile (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper discusses the translation of opera libretti throughout the history of the genre. Opera was born of a need to make words more prominent in vocal music and to express emotions through their musical setting. We shall first consider how attitudes to languages and to the audiences have impacted on different ways of providing translated versions of the operatic text through its relatively short history. Then, we shall focus on the most recent form of transfer available, on surtitling, show how it is governed by a desire for accessibility and is provided within the context of making classical music available to a wider and more diversified public.